Into the still blue - Rossi, Veronica. ([Under the never sky ;, 2014)
"In their effort to reach the fabled Still Blue, Aria and Perry will have to rescue Cinder, defeat Sable and Hess, and unite the Dwellers and the Outsiders once and for all"--